2019
DOI: 10.1037/lat0000117
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the promotive role of familism in the link between ethnic-racial identity and Latino youth school engagement.

Abstract: The present study assessed how ethnic-racial identity (ERI) and familism promote beneficial academic outcomes in Latino/a youth. In particular, we examined how ERI exploration and resolution were associated with school engagement through youths’ endorsement of the cultural value of familism. Data were drawn from a study of 148 Latino/a adolescents (79% U.S.-born, 53% girls) in the Midwestern region of the United States. Adolescent ERI exploration was associated with emotional, cognitive, and behavioral school … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 54 publications
(134 reference statements)
3
13
0
Order By: Relevance
“…Nevertheless, research examining how ethnic–racial identity relates to academic engagement specifically among Native American adolescents remains a grossly understudied area (Rivas-Drake et al, 2014). Thus, the present study’s findings contribute to previous literature on adolescents’ ethnic–racial identity and academic engagement (Butler-Barnes et al, 2013; Constante et al, 2019; Rivas-Drake, 2011) and support our first hypothesis by demonstrating that greater centrality and more positive regard were related to greater classroom engagement among Native American youth. Ethnic–racial identity development is a salient hallmark of the adolescence period (Umaña-Taylor et al, 2014) and may play a major role in predicting positive attitudes toward schools by combating the impact of various negative experiences adolescents face (Berkel et al, 2010; Rivas-Drake et al, 2014).…”
Section: Discussionsupporting
confidence: 87%
“…Nevertheless, research examining how ethnic–racial identity relates to academic engagement specifically among Native American adolescents remains a grossly understudied area (Rivas-Drake et al, 2014). Thus, the present study’s findings contribute to previous literature on adolescents’ ethnic–racial identity and academic engagement (Butler-Barnes et al, 2013; Constante et al, 2019; Rivas-Drake, 2011) and support our first hypothesis by demonstrating that greater centrality and more positive regard were related to greater classroom engagement among Native American youth. Ethnic–racial identity development is a salient hallmark of the adolescence period (Umaña-Taylor et al, 2014) and may play a major role in predicting positive attitudes toward schools by combating the impact of various negative experiences adolescents face (Berkel et al, 2010; Rivas-Drake et al, 2014).…”
Section: Discussionsupporting
confidence: 87%
“…Indeed, MIBI-based measures are less robustly associated with academic outcomes (Rivas-Drake et al, 2014). Or, it may be that other aspects of ethnic-racial identity are more critical to familism values like ethnic-racial exploration and resolution (Constante, Marchand, Cross, & Rivas-Drake, 2018; Streit et al, 2018) and familism may serve as a mediator of these aspects of ethnic-racial identity. Indeed, in a cross-sectional analysis, Constante et al (2018) found support for an indirect effect of ethnic identity exploration through familism on academic cognitive, emotional, and behavioral engagement.…”
Section: Discussionmentioning
confidence: 99%
“…Or, it may be that other aspects of ethnic-racial identity are more critical to familism values like ethnic-racial exploration and resolution (Constante, Marchand, Cross, & Rivas-Drake, 2018; Streit et al, 2018) and familism may serve as a mediator of these aspects of ethnic-racial identity. Indeed, in a cross-sectional analysis, Constante et al (2018) found support for an indirect effect of ethnic identity exploration through familism on academic cognitive, emotional, and behavioral engagement. Taken together, it is clear that ethnic-racial identity and cultural endorsement influence adaptation in Latinx families, and more work should continue to disentangle possible differential effects of various components of ethnic-racial identity and related processes over time and with distinct outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Relatively little is known about how the relationships between familismo and academic outcomes play out in emerging adulthood in the college context for Latinx undergraduates. Research investigating the relations between familismo and academic outcomes thus far has focused on Latinx middle and high school students (e.g., Aretakis et al, 2015; Constante et al, 2019; Esparza & Sánchez, 2008; Toyokawa & Toyokawa, 2019; Valenzuela & Dornbusch, 1994; cf. Ovink, 2014).…”
Section: Introductionmentioning
confidence: 99%